Microbial community structure in disease-suppressive soils as revealed by metabarcoding - López Alvarez, Diana; Pardo, Juan Manuel; Leiva Sandoval, Ana Maria; Álvarez, Elizabeth; Ceballos, German; Cuéllar, Wilmer Jose (2021)
Plant diseases caused by soil-borne bacterial pathogens result in significant yield losses and these pathogens are the most difficult to control due to their persistence in debris and soil. Enhancement of soil-natural disease suppression could be an effective option to control these diseases through soil management practices. The suppression of soil-borne diseases of soil microbial bacteria and fungi communities was analyzed in soils suppressive and non-suppressive for Moko disease caused by Ralstonia solanacearum in Quindío, Colombia, using bacterial tag-encoded FLX titanium amplicon pyrosequencing (bTEFAP) targeting 16Sr RNA and ITS genes.